The Impact of Grammar on the Construal of Discourse Alternatives in German and English - Dimroth, Christine; Starren, Marianne (Languages (Basel), 2022)
This paper investigates additive links to discourse alternatives in picture comparison dialogues produced by adult native speakers of English and German. Additive relations are established across turns when participants are confirming the presence of matching objects on both pictures (A: “I have X”. B: “I also have X”). Speakers thereby describe their own picture and construe the interlocutor (or rather: the interlocutor’s picture) as a discourse alternative. Whereas the vast majority of the confirming descriptions in German contain an additive particle (auch), less than half of the corresponding confirmations in the English data do (“also”, “too”, etc.). Numbers differ even more drastically in polarity questions (“Do you (also) have X?”) that are equally typical for the dialogue task. Such frequency differences are at odds with recent accounts treating additive particles as being quasi obligatory when their presupposition is satisfied. An in-depth contrastive analysis of lexical, syntactic and information structural properties reveals that the default mapping of information units on syntactic functions (subject) in conjunction with the SVO word order of English leads to a structure in which subject, initial (topic) position and the particle’s associated constituent coincide. This would make the relation to its discourse alternative more prominent than warranted by the dialogue task and speakers of English leave this relation unmarked or resort to alternative constructions instead. The V2 syntax of German, on the other hand, allows for a dissociation of discourse topic and associated constituent. It allows the speaker to topicalize reference to the matching object, to highlight the confirmation of its presence on the speaker’s picture, and to relate the changing information to its discourse alternative in a non-contrastive way.